2013
DOI: 10.1186/2193-1801-2-583
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of ethanol production by ethanol-tolerant Saccharomyces cerevisiae UVNR56

Abstract: Ethanol tolerance is one of the important characteristics of ethanol-producing yeast. This study focused on the improvement of ethanol tolerance of Saccharomyces cerevisiae NR1 for enhancing ethanol production by random UV-C mutagenesis. One ethanol-tolerant mutant, UVNR56, displayed a significantly improved ethanol tolerance in the presence of 15% (v/v) ethanol and showed a considerably higher viability during ethanol fermentation from sugarcane molasses and sugarcane molasses with initial ethanol supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…The production rate is in agreement with the previous studies [35, 36]. In a recent study, Thammasittirong et al reported 8.6% ( v/v ) production for wild-type strain [37]. …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The production rate is in agreement with the previous studies [35, 36]. In a recent study, Thammasittirong et al reported 8.6% ( v/v ) production for wild-type strain [37]. …”
Section: Resultssupporting
confidence: 91%
“…Like the palm wine yeast, TBY1 and TGY2 isolates exhibited remarkably high ethanol tolerance comparable to industrial yeasts such as sake and distiller’s yeasts associated with high level of ethanol tolerance [51, 52]. The level of ethanol tolerance of 15% ( v/v ) by the yeast strain UVNR56 [37] is in agreement with previous studies [53, 54]. In our present study, we have seen the similar result for Pa and Or isolates that tolerated up to 12% ethanol, which is much more consistent with the other results ( Tables 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…While day 6 colony-forming units at a 20 wt % solids loading to SSF dropped by about one order of magnitude, colony-forming units at solids loadings of 21.5 wt % and 23 wt % dropped by about three orders of magnitude. The decreased viability can be related with loss of membrane integrity as ethanol titers exceeded 80 g•L −1 due to hyperpolarization of phospholipid cell membranes and resulting greater fluidity and permeability (35). These results are in agreement with the fedbatch glucose fermentations, in that the highest ethanol yields were achieved at 20 wt % solids, where the glucose release was balanced with glucose consumption and ethanol toxicity to maintain greater cell viability.…”
Section: Resultssupporting
confidence: 81%
“…The highest amount of bioethanol production was 7% (v/v) in aerobic conditions and 8% (v/v) in aerobic-anaerobic conditions after 72 h. Therefore, the aerobic-anaerobic conditions are suitable for bioethanol production, because biomass was propagated in aerobic conditions and anaerobic conditions are suitable for alcoholic fermentation and ethanol production. Thammasittirong et al produced 8.6% (v/v) ethanol in a medium containing molasses with 28% Brix by S. cerevisiae NR1 [24].…”
Section: Discussionmentioning
confidence: 99%